Problematic Patient - KIRPINAR, İSMET; KIRPINAR, İSMET; Ayhan, M. Suhan; GÜNEREN, Ethem; GÜNEREN, ETHEM (My University, 2021)
The group of patients defined as -problematic patient- in aesthetic plastic surgical practice has distinctive features. The -problematic patient- is the patient who blocks the establishment of a therapeutic relationship with him/her. In other words, the patient who does not adapt to the patient role that the health-care professional expects, has different values, beliefs, or personal characteristics than he/she expects to see, and sometimes causes the professional to even suspect himself/herself. They are not good candidates for esthetic surgery, and they should definitely not be operated, so to speak, these patients should be removed from the game by removing a red card, and somehow be disqualified from the process.